Development of erythropoietin receptor-targeted drug delivery system against breast cancer using tamoxifen-loade nanostructured lipid carriers - Beh, Chaw Yee; How, Chee Wun; Foo, Jhi Biau; Foong, Jia Ning; Selvarajah, Gayathri Thevi; Abdullah, Rasedee (Dove Medical Press, 2017)
Tamoxifen (TAM) has been used in the treatment of breast cancers and is supplemented with erythropoietin (EPO) to alleviate the cancer-related anemia. The purported deleterious effects caused by the use of EPO with chemotherapeutic agents in the treatment of cancer-related anemia vary across studies and remain controversial. The use of nanoparticles as a drug delivery system has the potential to improve the specificity of anticancer drugs. In this study, we simultaneously incorporated two pharmacological active ingredients in one nanocarrier to develop EPO-conjugated TAM-loaded lipid nanoparticles (EPO-TAMNLC), a targeted delivery system, to enhance the cytotoxic activity while reducing the side effects of the ingredients. The effect of temperature in modulating the thermodynamic parameters associated with the binding of EPO and TAMNLC was assessed using isothermal titration calorimetry, while the unfolding of EPO structure was determined using fluorescence-quenching approach. The association efficiency of EPO and TAMNLC was 55.43%. Unlike binding of albumin to TAMNLC, the binding of EPO to TAMNLC occurred through endothermic and entropy-driven reaction. The EPO-TAMNLC formulation was stable because of the hydrophobic interaction and the high free energy, suggesting the spontaneity of the interactions between EPO and TAMNLC. The EPO-TAMNLC enhanced the in vitro cytotoxicity of TAM to MCF-7 cells. The EPO surface-functionalized TAMNLC could sequentially deliver EPO and TAM as well as improving site-specific delivery of these therapeutic compounds.